PENGARUH PENAMBAHAN ARANG SEKAM PADI TERHADAP PERTUMBUHAN CABAI RAWIT (Capsicum frutescens L.) DI KEBUN PENDIDIKAN BIOLOGI UNIVERSITAS HAMZANWADI TAHUN 2020 - Muliawan, Wawan (UNIVERSITAS HAMZANWADI, 2020)
The purpose of this study was to determine the effect of adding husk charcoal on the growth of cayenne pepper (Capsicum frustescens L.). This research is an experimental study by looking at the effect of adding husk charcoal to chili growth using a Completely Randomized Design (CRD). The statistical data analysis test used was ANOVA 1 ROAD with a significant level of 5% and used rice husk charcoal of 250 grams, 500 grams, 750 grams. The results of the data analysis of plant height Fcount> Ftable (6.08> 2.92), leaf length Fcount> Ftable (9.66> 2.29) and the number of leaves Fcount <Ftable (1.04 <2.92). It can be concluded that there is an effect between treatments on the parameters of height and leaf length growth whereas the number of leaves has no effect. The best growth of cayenne pepper can be seen in the addition of husk charcoal at a rate of 250 grams.Keywords: Husk charcoal media, growth of cayenne pepper (Capsicum Frustescens L).